Morphological Analysis of Derivational and Inflectional Affixes from Meghan Trainor's Selected Song - Istama, Nanda Rizka; Nargis; Sutikno, Eka Ugi (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the use of derivational and inflectional affixes in selected songs by Meghan Trainor. Using a qualitative descriptive approach, the study analyzes 10 of Trainor’s songs to identify and classify affixes based on their morphological functions. The results show that inflectional affixes dominate the lyrics, with a total of 77 occurrences compared to 27 derivational affixes. This indicates that the lyrics frequently feature inflectional affixes to convey grammatical functions such as tenses, plurality, and comparison. This finding may suggest a tendency in similar English pop lyrics tend to use inflectional affixes to maintain grammatical structure while supporting rhythmic flow.